Primary squamous cell carcinoma of pancreas mimicking walled-off pancreatic necrosis - Deepak Gunjan; Surinder Singh Rana; Puneet Chhabra; Rahul Vithalrao Parghane; Rajesh Kumar; Lovneet Dhalaria; Bhawant R. Mittal; Deepak K. Bhasin (Journal of Digestive Endoscopy, 2016)
Pancreatic carcinoma is a dreaded diagnosis due to its poor prognosis. Squamous cell carcinoma (SCC) of the pancreas is a rare histological variety of pancreatic carcinoma. Its diagnosis is based on ruling out other site of tumor origin. Pancreatic carcinoma can mimic as mass or cystic lesion. We report a case of primary SCC of the pancreas in a 46-year-old male that closely mimicked acute pancreatitis with walled-off pancreatic necrosis.